Penanaman Nilai Tradisi Kepesantrenan Dalam Membendung Radikalisme Agama - Khairunnisa Khairunnisa (LPPM IAIN Sorong, 2020)
Kitab Kuning tradition conserved by boarding schools recently is identical as a place of terrorism, and of course the stigma is a very erroneous reading. Boarding School is viewed with suspicion, stigmatic, so the boarding school institution as the